(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article is devoted to the importance of industrial design in production. The impact of design on product production is revealed, and the main directions of the technical designer’s activity in the modern world are described. The development of ergodesign and the formation of style in different countries are described.